Accounting Education and Training in Asean: The Western lnï¬‚uence and The Experience of Sin - Yapa, P. W. Senarath (Accounting Department,, 1998)
This paper provides an analysis of the nature of accounting education and training in four ASEAN countries- Singapore. Malaysia. Indonesia, and Brunei Darussalam. All these countries were under colonial rule for centuries. Therefore, it provides a review of inï¬‚uence by their colonial powers in accounting education and training and gain insight into why sortie countries are still following the colonial system while others have shifted away. As evidenced however, while Singapore has shown signs of moving away from colonial system, Malaysia seems to be in the process of such a move. Apparently, lndonesia has moved from the Dutch to the US system in its accounting education and training. Brunei Darussalam is still in rudimentary stage of its accounting development and following the British system of accounting education to produce accountants. This paper indicates that if a developing country continues to depend heavily on colonial system of accounting education without considering the local environment, institutions and the local needs, the consequences can be less than desirable. Keywords: Accounting education and practice, Professional accounting bodies, Colonial inï¬‚uence, Association of South East Asian Nations (ASEAN), Accounting in developing countries.